2018
DOI: 10.1155/2018/2321361
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on Drying‐Wetting Cycle Characteristics of Expansive Soils Improved by Industrial Wastes

Abstract: The improved engineering properties of the expansive soil by mixing with various additives will be changed during the long-term variation of the meteorological and hydrological conditions. In the present work, a series of tests are performed to investigate the evolution of the unconfined compression strength and the Atterberg limits under drying-wetting cycling conditions for specimens treated by iron tailing sands and calcium carbide slag. Typical results of the unconfined compressive strength can be divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 16 publications
4
15
0
Order By: Relevance
“…Ma et al [21] used nuclear magnetic resonance (NMR) technology to study the change law of water content in the drywet cycle and explained the change mechanism of the pore in SWCC. Whereafter, some scholars studied SWCC under complex conditions such as dry-wet cycle and freeze-thaw cycle [22][23][24][25][26][27][28][29]. It can be seen that these studies are aimed at the expansive soil in a particular area, and the SWCCs of expansive soils in different areas have different laws under the external conditions such as dry-wet cycle and freezethaw cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [21] used nuclear magnetic resonance (NMR) technology to study the change law of water content in the drywet cycle and explained the change mechanism of the pore in SWCC. Whereafter, some scholars studied SWCC under complex conditions such as dry-wet cycle and freeze-thaw cycle [22][23][24][25][26][27][28][29]. It can be seen that these studies are aimed at the expansive soil in a particular area, and the SWCCs of expansive soils in different areas have different laws under the external conditions such as dry-wet cycle and freezethaw cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Rao et al [14] observed a negative effect of the W-D cycles on lime-stabilized and wood-ash-modified black cotton soil. Ye et al [15] described variations in the unconfined compression strength and the Atterberg limits of expansive soils improved by industrial wastes with the W-D cycles. Wang et al [16] showed that the strength of expansive soil improved by 0.3% OTAC (octadecyl trimethyl ammonium chloride)-3%KCL lost gradually with the W-D cycles.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, as environmental protection issues have drawn increasing attention, scholars have started to use various types of solid wastes as additives for expansive soil stabilization [12], such as fly ash [13], blast furnace slag [14,15], cement kiln dust [16,17], waste foam particle [18], alkali residue [19], and so on. Sometimes, some wastes can also be mixed with cementitious material during stabilization of expansive soil, for example, fly ash and lime [20,21], bagasse ash and lime [22], natural volcanic ash and lime [23], phosphogypsum and lime [24], ground granulated blastfurnace slag and lime [25], iron tailing sands, and calcium carbide slag [26]. ese mixtures can achieve better results than cementitious material alone.…”
Section: Introductionmentioning
confidence: 99%